Conjunctival keratoacanthoma - Schellini, Silvana Artioli [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Milanezi, Maria Fernanda Grillo [UNESP]; Bacchi, Carlos E. [UNESP] (My University, 1997)
Keratoacanthoma is a rapidly growing skin neoplasia that may stabilize or regress spontaneously. We describe here a case of conjunctival keratoacanthoma and comment about the clinical signs and symptoms and pathological findings.
Keywords: Conjunctival keratoacanthoma; Conjunctival tumor; Histopathology (conjunctival keratoacanthoma); Immunohistochemistry (conjunctival keratoacanthoma); adult; case report; clinical feature; conjunctiva tumor; female; histopathology; human; human tissue; keratoacanthoma; priority journal; symptom; wart virus; Adult; Conjunctiva; Conjunctival Diseases; Female; Humans; Immunohistochemistry; Keratoacanthoma; Skin Diseases